Meet your soul - "Arora, Ashok" (New Delhi, 2010)
The real beauty of this book is that one can follow the simple route the author has formulated to lead a blissful life. One just has to understand and be aware of the issues discussed by him. It is not a bad bargain to have a peaceful and successful life by just spending an hour every day as per his suggestions.
Keywords: Successful life